Contemporary boron chemistry - Davidson, Matthew (Special publication, 2000)
The continued and evolving significance of boron chemistry to the wider chemical community is demonstrated by the international and interdisciplinary nature of the research reported in this book. Contemporary Boron Chemistry encompasses inorganic and organic compounds as well as polymers, solid-state materials, medicinal aspects and theoretical studies. Covering many areas of chemistry with boron at its centre, topics include applications to polyolefin catalysis, medicine, materials and polymers; boron cluster chemistry, including carboranes and metal-containing clusters; organic and inorganic chemistry of species containing only 1 or 2 boron atoms; and theoretical studies of boron-containing compounds. New materials with novel optical and electronic properties are also discussed. Comprehensive and up to date, graduates and researchers in a wide range of fields, particularly those in organometallic and organic chemistry and materials science, will welcome this book